2009
DOI: 10.5254/1.3548250
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Structural Characterization of Natural Rubber

Abstract: Structural characterization of rubber from Hevea brasiliensis (NR) has been carried out to elucidate the biosynthesis mechanism of rubber molecule as well as to find the relationship between physical properties characteristic of NR and its structure. Recent advances of structural studies have provided a series of new information on the structure of long-chain branching based on the result of selective decomposition of branch-points by chemical and enzymatic treatments as well as physical treatment such as pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 0 publications
3
75
0
Order By: Relevance
“…Interestingly, the crosslink density of a macrogel exponentially increases with its protein concentration (R 2 = 0.967). Several studies have already suggested that proteins are partly responsible for the presence of macrogel in NR samples [14,21]. Our results showed that proteins play a major role in the structuring of a macrogel, and seem to be involved in the majority of crosslinks.…”
Section: 4supporting
confidence: 53%
See 4 more Smart Citations
“…Interestingly, the crosslink density of a macrogel exponentially increases with its protein concentration (R 2 = 0.967). Several studies have already suggested that proteins are partly responsible for the presence of macrogel in NR samples [14,21]. Our results showed that proteins play a major role in the structuring of a macrogel, and seem to be involved in the majority of crosslinks.…”
Section: 4supporting
confidence: 53%
“…Our results showed that proteins play a major role in the structuring of a macrogel, and seem to be involved in the majority of crosslinks. The influence of esterified lipids on the presence of macrogel has also been reported [21,22]. In this paper, we have shown that extractable lipids amounted to less than 0.5% (w/w) for macrogels with low protein concentrations and could be neglected compared to proteins.…”
Section: 4mentioning
confidence: 65%
See 3 more Smart Citations